2019
DOI: 10.1038/s41590-019-0378-1
|View full text |Cite
|
Sign up to set email alerts
|

Defining inflammatory cell states in rheumatoid arthritis joint synovial tissues by integrating single-cell transcriptomics and mass cytometry

Abstract: To define the cell populations that drive joint inflammation in rheumatoid arthritis (RA), we applied single-cell RNA sequencing (scRNA-seq), mass cytometry, bulk RNA-seq and flow cytometry to T cells, B cells, monocytes and fibroblasts from 51 samples of synovial tissue from patients with RA or osteoarthritis. Utilizing an integrated strategy based on canonical correlation analysis of 5,265 scRNA-seq profiles, we identified 18 unique cell populations. Combining mass cytometry and transcriptomics together reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
913
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 857 publications
(1,067 citation statements)
references
References 56 publications
56
913
2
1
Order By: Relevance
“…This observation was shown independently by another group that classified two subtypes of macrophages in OA (55). Furthermore, AMP characterized myeloid subpopulations from joint replacements and compared the transcriptional profile of macrophages from OA and RA patients (43). In particular, their OA macrophages exhibited increased expression of genes that were down-regulated in our data.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This observation was shown independently by another group that classified two subtypes of macrophages in OA (55). Furthermore, AMP characterized myeloid subpopulations from joint replacements and compared the transcriptional profile of macrophages from OA and RA patients (43). In particular, their OA macrophages exhibited increased expression of genes that were down-regulated in our data.…”
Section: Discussionsupporting
confidence: 79%
“…Figure 3D). This may indicate that OAassociated inflammation is distinct from that observed in RA (43). Therefore, these results suggest that synovial macrophages increase expression of genes associated with OA-specific inflammation and monocyte infiltration, while decreasing expression of genes associated with the tissue-resident phenotype.…”
Section: Synovial Macrophages Exhibit a Peak Inflammatory Response Inmentioning
confidence: 78%
See 1 more Smart Citation
“…This was accompanied by reductions in synovial cellularity, joint damage, and leukocyte infiltration, highlighting that the changes observed were not solely due to a reduction in the number of cells within the synovium. Bulk-sequencing of sorted populations mirrored the findings of Zhang et al (41), with the largest differences being observed between the lining layer and sublining layer (45). Further similarities existed in the gene expression profile of these populations with the FAPα + CD90 + cells expressing higher levels of chemokines and cytokines, including IL-6, whereas the FAPα + CD90 − cells showed higher levels of RANKL and MMPs.…”
Section: Single Cell Approaches To Synovial Tissue Analysissupporting
confidence: 69%
“…Within the NIH AMP consortium, the exploration of synovial fibroblast subsets was extended through a combined investigation of larger numbers of RA and OA samples using bulk and scRNA-seq, and flow and mass-cytometry. Zhang et al (41) used canonical correlation analysis to integrate this multimodal data from 51 RA and OA samples, facilitating a linked transcriptomic and proteomic analysis of single cells. In addition to defining the myeloid, T and B cell subpopulations present in the RA synovium, this study identified four synovial fibroblast populations: a CD55 + lining layer population and three sublining populations identified as CD34 + , HLA hi , or DKK3 + .…”
Section: Single Cell Approaches To Synovial Tissue Analysismentioning
confidence: 99%